Use of intraoperative fluorescence to enhance robot-assisted radical prostatectomy - Rajakumar, Timothy; Yassin, Musaab; Musbahi, Omar; Harris, Eli; Lopez, J Francisco; Bryant, Richard J; Tullis, Iain Dc; Vojnovic, Borivoj; Hamdy, Freddie C; Lamb, Alastair D (Future oncology (London, England), 2021)
Robot-assisted radical prostatectomy has become the standard of care for the removal of localized prostate cancer. Positive outcomes depend upon the precise removal of the prostate and associated tissue without damage to nearby structures. This process can be aided by fluorescence-guided surgery to enhance the visual contrast between different structures. Here the authors have conducted a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to identify ten investigations into the use of fluorescence-guided surgery in robot-assisted radical prostatectomy. These studies used fluorescent tracers to identify structures, including the prostate, neurovascular bundle and lymph nodes. These studies demonstrate the safe and effective use of fluorescence-guided surgery in robot-assisted radical prostatectomy and pave the way for further developments in this field.